Analysis of Internal and External Environment towards Competitive Advantage and Performance of SMEs Klambir V - Hasrul Azwar Hasibuan; Nashrudin Setiawan; Virlanda Ashara (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This study aims to investigate how the use of digital technologies, including e-commerce and social media, can play an important role in enhancing the influence of business strategy on the performance of Micro, Small and Medium Enterprises (MSMEs). This study will evaluate whether digital technology acts as an intermediary that facilitates the positive impact of business strategy on MSME performance in Klambir V Kecamtan Hamparan Perak. This research uses a quantitative approach with an explanatory research design, observation and questionnaire methods, with purposive sampling of food and culinary products located around Klambir V District. The analytical tool used is Multiple Regression. Population and sample of SMEs as many as 55 SMEs.